Discussing advance care planning: insights from older people living in nursing homes and from family members. (9th October 2017) - Ingravallo, Francesca; Mignani, Veronica; Mariani, Elena; Ottoboni, Giovanni; Melon, Marie Christine; Chattat, Rabih
ABSTRACT: Background: Evidence concerning when and in which manner older people living in nursing homes (NHs) would prefer to discuss advance care planning (ACP) is still scarce. This study explored the attitudes of NH residents and family members toward ACP and their opinions as to the right time to broach the subject, the manner in which it should be approached, and the content of ACP. Methods: This was a qualitative study using face-to-face interviews with 30 residents (age range 66–94), and 10 family members from 4 Italian NHs. The interviews were analyzed using content analysis. Results: Three main themes were identified: (1) life in the NH, including thoughts about life in a nursing home, residents' concerns, wishes and fears, and communication barriers; (2) future plans and attitudes toward ACP, including attitudes toward planning for the future and plans already made, and attitudes toward and barriers against ACP; (3) contents and manner of ACP, including contents of ACP discussions, the right moment to introduce ACP, with whom it is better to discuss ACP, and attitudes toward advance directives. Conclusions: ACP was a welcome intervention for the majority of participants, but an individualized assessment of the person's readiness to be involved in ACP is needed. For people with dementia, it is essential to identify the right time to introduce ACP before NH admission. Participants in our study suggested that ACP should include palliative care and practical issues, and that in the NH setting all staff and family members may have a valuable role in ACP.